ABOUT THE CAMPAIGN OF IMAMKULI KHAN OF BUKHARA IN 1619 (Western European Journal of Historical Events and Social Science, 2025)
This article analyzes the political relations between Imamqulikhan (1611–1642), a prominent representative of the Ashtarkhanid dynasty, and Kazakh sultans such as Yeshim Khan, Tursun Khan, and Abulai Sultan. Until the 1620s, the Bukhara Khanate was in competition with the Kazakh sultans over the territories of Tashkent, the banks of the Syr Darya, and the Ferghana Valley. The political processes of this period are comprehensively covered based on primary sources